Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Keterampilan Kolaboratif dan Self-Efficacy pada Pembelajaran IPS - Silvia Eka Nur Wulandari; Warsono Warsono; Ketut Prasetyo (Universitas Hamzanwadi, 2026)
This research is motivated by the low level of collaborative skills and self-efficacy of students in social studies learning due to the dominance of conventional methods that are not aligned with the multidimensional and interpretive epistemology of social studies. This study aims to analyze the effectiveness of the Student Teams-Achievement Divisions (STAD) cooperative learning model in improving students' collaborative skills and self-efficacy in social studies learning, specifically on the topic of Social Conflict and Integration. This study employed a quantitative approach with a quasi-experimental non-equivalent control group design. The population was eighth-grade students of SMP Negeri 2 Sidoarjo, with two classes selected using purposive sampling: an experimental class (n=37) using the STAD model and a control class (n=37) using a simple cooperative model. The research instruments included a collaborative skills observation sheet and a self-efficacy questionnaire that had been validated. Data analysis techniques used the Independent Sample T-Test and N-Gain test. The results showed that the STAD model was significantly more effective than the simple cooperative model. The mean post-test score for collaborative skills in the experimental class (78.00) was higher than that of the control class (75.11), with a significance value of 0.000 (p<0.05). The mean post-test score for self-efficacy in the experimental class (87.11) was also much higher than that of the control class (69.46) (p<0.05). The N-Gain test confirmed the effectiveness of the STAD model in the moderate to high category for both variables. This study concludes that the integration of the STAD cooperative learning model is effective in simultaneously improving students' collaborative skills and self-efficacy. It provides a theoretical contribution to the development of learning models based on social and cognitive constructivism, as well as a practical contribution for social studies teachers in implementing innovative 21st-century learning.